Detection of DNA Amplicons of Polymerase Chain Reaction Using Litmus Test - Dingran Chang (Nature Portfolio, 2017)
Abstract We report on a new colorimetric DNA detection method that takes advantage of the power of polymerase chain reaction (PCR) and the simplicity of the classic litmus test. The strategy makes use of a modified set of primers for PCR to facilitate ensuing manipulations of resultant DNA amplicons: their tagging with urease and immobilization onto magnetic beads. The amplicon/urease-laden beads are then used to hydrolyze urea, resulting in the increase of pH that can be conveniently reported by a pH-sensitive dye. We have successfully applied this strategy for the detection of two hypervirulent strains of the bacterium Clostridium difficile that are responsible for the recent increase in the global incidence and severity of C. difficile infections. Furthermore, the viability of this test for diagnostic applications is demonstrated using clinically validated stool samples from C. difficile infected patients.